NUTRITIONAL ASSESSMENT OF PATIENTS WITH ADVANCED CHRONIC RENAL FAILURE (Iraqi Journal of Medical Sciences, 2004)
Background: Malnutrition is an important risk factor for morbidity and mortality in patients with advanced chronic renal failure. Its prevalence has been estimated to range from 10 to 70% in patients on maintenance hemodialysis and 18 to 51% in patients treated by CAPD. Objective: is to assess the nutritional status of patients with advanced chronic renal failure treated in the University Hospital including those on maintenance hemodialysis and those treated conservatively who underwent peritoneal dialysis as a life saving procedure. Patients & Methods: Fifty patients (25 on regular hemodialysis and 25 with chronic renal failure in whom peritoneal dialysis was done as an acute procedure) were studied. Their state of nutrition was assessed clinically, biochemically and by anthropometric measurements. Results: The dietary intake was inadequate in 44 (88%) patients. Thirty-eight (76%) patients had clinically evident muscle wasting.Body mass index, triceps skin fold thickness and mid-arm muscle circumference were below the standard in 62%, 82%, and 74% of patients respectively. Forty-seven (94%) patients were anemic. Albumin level was less than 4.0 gm/dl in 32 (64%) patients. Conclusion: Malnutrition is common in our patients with advanced chronic renal failure. Simple anthropometric measurements are valuable in its diagnosis. Keywords: nutrition, malnutrition, chronic renal failure, and dialysis. Iraqi J Med Sci, 2004; Vol. 3 (1): 38-42